2010
DOI: 10.1002/app.32521
|View full text |Cite
|
Sign up to set email alerts
|

Structure and properties of phase change materials based on HDPE, soft Fischer‐Tropsch paraffin wax, and wood flour

Abstract: Phase-change materials based on high density polyethylene (HDPE), soft Fischer-Tropsch paraffin wax (M3), and alkali-treated wood flour (WF) were investigated. The blend and composite samples were prepared by melt mixing using a Brabender Plastograph, followed by melt pressing. They were characterized in terms of their morphology, as well as thermal, mechanical, thermomechanical, and water absorption properties. Although SEM micrographs showed some evidence of intimate contact between the WF particles and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
25
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 34 publications
1
25
1
1
Order By: Relevance
“…The position of the observed additional peak at −14°C for the blend composites seems to depend on the H1 wax content. As in our previous work on soft wax‐based blend composites [31], we could not find an explanation for the origin of this transition.…”
Section: Resultscontrasting
confidence: 81%
See 2 more Smart Citations
“…The position of the observed additional peak at −14°C for the blend composites seems to depend on the H1 wax content. As in our previous work on soft wax‐based blend composites [31], we could not find an explanation for the origin of this transition.…”
Section: Resultscontrasting
confidence: 81%
“…The water uptake of these composites also decreases with an increase in wax content. As in the case of M3 wax‐containing composites [31], this is the result of the affinity between the wax and the WF, which shields the WF particles from the water and which reduces the number of voids in and around the WF particles. The water uptake of the 10% WF‐containing composites is clearly lower than that of the 20% WF‐containing composites.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the presence, type and amount of the filler particles did not change the melting behaviour of PE or wax in the composites. A limited amount of research has been done on the dynamic mechanical properties of polymer/wax blend composites [11,13]. When expanded graphite was used as filler, an increase in storage modulus was observed with an increase in filler content, which was an indication that the filler reinforced the matrix and countered the softening effect of the wax [13].…”
mentioning
confidence: 99%
“…No specific trends related to the amount of filler particles were observed. However, the presence of wood filler particles in the polymer/wax blends reduced the storage modulus [11]. The thermal conductivity of form-stable PCM composites was investigated in a number of studies [5,[12][13][14][15].…”
mentioning
confidence: 99%